Irreversibility and First and Second Law Efficiencies Analysis in three different Solar Cookers Box-Type. Issue 1 (January 2021) - Terres, H; Chávez, S; Lizardi, A; López, R; Vaca, M; Lara, A; Morales, J
Abstract: This work shows the results and evaluation of three box-type solar cookers. The cooker designs are octagonal, rectangular and square. Irreversibility, first and second law results are obtained considering the water heating process. These values indicate that the rectangular design has the highest efficiency values, although it does not have the highest temperature values. It is shown how the area of the glass cover of the cookers influences its efficiency since the increase in this value is not reflected in an improvement in efficiency. The effect of irreversibility and its impact over the second-law efficiency when the water heating process increases in the solar cookers are explained. The results are very useful because they allow us to assess the potential ranges of exergy when it is applied to energy devices such as solar cookers, which can contribute to the design and improvement of solar devices with the same characteristics.